2021
DOI: 10.3389/fpsyt.2020.599241
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Smartphone Use—Comparison of Students With and Without Problematic Smartphone Use in Light of Personality

Abstract: Background: As a device with multiple functions, a smartphone become more and more relevant in everyday life. However, this goes along with an increase in reports about smartphone addiction and its unwanted consequences. One of the most important variables in the etiopathogenesis of addictive smartphone use is personality.Objective: This study aimed to investigate predictors of problematic smartphone use. Clinically relevant differences in personality, psychopathology, and social support between students with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Although amount of time alone should not be the sole criterion, it is one of the most dependable benchmarks in diagnosing PSU in extant research (Duke and Montag, 2017;Vahedi and Saiphoo, 2018;Sahu et al, 2019). The statistical distribution of this group (12.9%) fits well-nigh the overall estimate by Eichenberg et al (2021) in evaluating the prevalence rate of PSU at 15.1% in their study of college students in Vienna. Besides the prevailing tendency to stay longer on a variety of activities that the previous groups also engage in, close to one-half of them specifically mention mobile gaming as one of the most frequently accessed apps on their smartphone.…”
Section: Interviewee Demographics and User Typologymentioning
confidence: 77%
“…Although amount of time alone should not be the sole criterion, it is one of the most dependable benchmarks in diagnosing PSU in extant research (Duke and Montag, 2017;Vahedi and Saiphoo, 2018;Sahu et al, 2019). The statistical distribution of this group (12.9%) fits well-nigh the overall estimate by Eichenberg et al (2021) in evaluating the prevalence rate of PSU at 15.1% in their study of college students in Vienna. Besides the prevailing tendency to stay longer on a variety of activities that the previous groups also engage in, close to one-half of them specifically mention mobile gaming as one of the most frequently accessed apps on their smartphone.…”
Section: Interviewee Demographics and User Typologymentioning
confidence: 77%
“…Among them, alpha-beta-gamma spectral power is based on the frequency bands associated with IA summarized from previous studies. Compared with the traditional questionnaire analysis [25] and biostatistics method [26], we have obtained more convincing quantitative results, and the accuracy is higher than the current SVM algorithm used for diagnosing IA [27]. In particular, the CNN model achieves 87.59% accuracy, 88.80% sensitivity, and 86.41% specificity based on full spectral power data.…”
Section: Introductionmentioning
confidence: 89%
“…The scores of Extraversion were summed of the scores of item 1R and item 6, the scores of Agreeableness were combined with the scores of item 2 and 7R, Conscientiousness as 3R and 8, Neuroticism as 4R+9, and Openness as 5R+10 (R = item is reversed-scored). Several studies have shown that BFI-10 has good reliability and validity ( 27 29 ). In a previous study, the reliability levels of the BFI-10 proved satisfactory using Cronbach's α analysis: Extraversion (α = 0.723), Agreeableness (α = 0.759), Conscientiousness (α = 0.786), Neuroticism (α = 0.753) and Openness to experience (α = 0.714) ( 30 ).…”
Section: Methodsmentioning
confidence: 99%